The Solvent in Physical Gelation: Polymers Versus Organogelators1. Issue 17 (7th June 2013) - Dasgupta, Debarshi; Guenet, Jean‐Michel; Milano, Giuseppe; Venditto, Vincenzo; Oliva, Leone
Abstract The mechanisms responsible for the physical gelation of polymers and of organogelators are discussed and compared. For polymers, the prerequisite for obtaining fibrillar thermoreversible gels is the impediment of chain folding. This occurs when polymers take on a worm‐like chain conformation with a large persistence length. This property can be intrinsic to the polymer, such as agarose, or can be obtained by the occurrence of polymer–solvent molecular compounds, as is the case for stereoregular polymers. For organogels, it is suggested that the mechanism for producing fibrils involves the much faster growth of one face of the organogel crystal structure with respect to the other two, which can be enhanced via specific interactions with the solvent, something reminiscent of molecular compounds.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>